The High Inspection of Education in comparative and historical perspective - Ramírez Aísa, Elías (Avances en Supervisión Educativa, 2022)
The department of the Inspectorate of Education for non-university education is an unknown institution. There are hardly any studies that identify its needs, content and history. The present work tries to approach these three aspects, paying special attention to the historical perspective. A historical perspective held on law compared to other countries, on our constitutional history and on the evolution of the rule that regulates the department of the Inspectorate of Education. All this without forgetting the political positions expressed in the parliamentary debate.
Keywords: State; Constitution; Department of the Inspectorate of Education; Supervision